(untitled) (Scientia Agricola, 2018)
The Mantiqueira Range region is one of the most important headwaters in southeastern Brazil. In this context, the relationship between pedology and hydrology has been debated and analyzed in recent years, contributing to the creation of a multidisciplinary science call hydropedology. Therefore, the aim of this study was to evaluate the hydropedological properties of a mountainous Clayey Humic Dystrudept in the Mantiqueira Range region, in the state of Minas Gerais, Brazil, comparing two land-uses, native forest and pasture. The hydraulic conductivity results demonstrated that native forest (MFO) has a strong influence on this parameter, offering conditions for movement of water in the soil that are more adequate in this profile than in pasture. These results were supported by pore size distribution analyses which showed that soil from native forest has a greater amount of macropores than soil from pasture as well as greater connectivity between the macropores. In general, the MFO site had greater S index values than the micro-catchment taken from pasture, offering favorable physical conditions for the formation of preferential flowpaths in the soil profile and, therefore, better conditions for groundwater recharge. Soil erosion and water quality results confirmed the importance of native forest areas in the interaction between interception of the direct impact of intense precipitation on the soil surface, and hydropedological attributes, such as saturated hydraulic conductivity and porosity.